Cryptic species and colonization processes in Ophryotrocha (Annelida, Dorvilleidae) inhabiting vertebrate remains in the shallow‐water Mediterranean. (20th March 2017) - Taboada, Sergi; Leiva, Carlos; Bas, Maria; Schult, Nancy; McHugh, Damhnait
Abstract : Over the past several years, there has been growing interest in how bones of decaying mammals are colonized in the marine seabed. One of the most common opportunistic taxa occurring worldwide on bones is dorvilleid polychaetes of the genus Ophryotrocha . In a recent study in the Mediterranean, Ophryotrocha puerilis and Ophryotrocha alborana were two of the most abundant species occurring in experimentally deployed bones. These species have direct development and this makes them a suitable model to study the mechanisms and processes allowing organisms lacking a dispersive larval phase to colonize new substrates. Here, we address the colonization processes at the molecular level for populations of O. puerilis and O. alborana on experimentally deployed mammal bones in the shallow‐water Mediterranean collected over a year at 3‐month intervals. High genetic distances between some of the O. puerilis organisms collected indicated the occurrence of at least two cryptic sibling species ( O. puerilis 'Shallow' and O. puerilis 'Deep') apart from O. puerilis sensu stricto . This was corroborated with phylogenetic analyses using an alignment of three concatenated genes ( COI, 16S, H3 ) and with species delimitation analyses using COI . The haplotype network inferred from COI sequences for O. puerilis 'Shallow' showed a few common haplotypes shared between the two trimesters analysed and several other less represented haplotypes only present in one trimester. Thus, colonization of these experimental bones may have been achieved by a few organisms that arrived to the bones and were able to reseed, and by several individuals arriving to the experimental bones and not persisting across time. In contrast, the haplotype network for O. alborana revealed that none of the haplotypes present in three different trimesters were shared, suggesting that the populations arriving at the bones during each trimester were totally replaced by new individuals during the subsequent trimesters. Our study suggests that different species of shallow‐water Ophryotrocha occurring in the Mediterranean may have different patterns of substrate colonization despite sharing similar life histories.